Pencegahan Risiko Infeksi Luka Perineum melalui Vulva Hygiene (Lembaga Pengembangan Kinerja Dosen, 2026)
The postpartum period is a critical phase with a high risk of complications, particularly perineal wound infection, especially in mothers with premature rupture of membranes (PROM). PROM increases the risk of microbial invasion into the birth canal, making infection prevention essential. Vulva hygiene is a non-pharmacological intervention that can help reduce this risk. This study aimed to evaluate the application of vulva hygiene in reducing the risk of perineal wound infection in postpartum mothers with PROM. This study used a case study design involving four postpartum mothers with PROM treated in the Wijaya Kusuma Ward of RSUD Limpung Batang in 2025. Data were collected through comprehensive nursing assessments, observation of perineal wound conditions, and evaluation of infection risk signs before and after the intervention. The results showed that regular implementation of vulva hygiene led to a reduction in infection risk signs, decreased perineal pain, and improved genital hygiene in all patients. Nursing education and assistance played a crucial role in the success of this intervention. It can be concluded that vulva hygiene is an effective nursing intervention in preventing perineal wound infection in postpartum mothers with PROM.